Effectiveness of Family Nutrition Education on the Incidence of Stunting: Systematic Review - Hardiyanti, Siti; Rekawati, Etty; Setiawan, Agus; Rahmadiyah, Dwi Cahya (Indonesian Journal of Global Health Research, 2024)
The family has an important role in the growth and development of babies so that they do not experience stunting. Knowledge has an impact on increasing understanding of toddler nutrition.Objective: The aim of this literature search is to determine the effectiveness of family nutrition education on the incidence of stunting. Literature search method by combining search term using Boolean operator, below are the keywords used in the literature “mother” AND “Family nutritional science” AND “stunting” OR “growth disorders”. Literature search on several databases: Sage Journal, PubMed, Clinical Key, Science Direct, Proquest, Ebsco, Embase, Springer Link published from January 2018 to December 2023 and found 75.261 article using the PRISMA method. This systematic review research study explains that family nutrition education has the aim of increasing family knowledge, healthy development, diversity of eating patterns, and increasing the growth and development of toddlers. Family nutrition education can increase knowledge and understanding regarding eating patterns and nutrition for toddlers, family nutrition education followed by training can further improve behavior in providing healthy nutrition for toddlers.